2005
DOI: 10.1063/1.2061856
|View full text |Cite
|
Sign up to set email alerts
|

Si-doped AlxGa1−xN(0.56⩽×⩽1) layers grown by molecular beam epitaxy with ammonia

Abstract: We describe experiments on Si doping in Al x Ga 1−x N grown by gas source molecular beam epitaxy with ammonia and silane. Growth conditions that minimize self-compensation were used to assure Si incorporation at a level of 2 ϫ 10 20 cm −3 for the entire range of compositions investigated, from x = 0.56 to 1.0. These conditions resulted in donor concentrations of ϳ1 ϫ 10 19 cm −3 up to x = 0.85. Layers of Al x Ga 1−x N up to x = 0.85 show good mobility and low resistivity. In these layers, the activation energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 21 publications
0
47
0
1
Order By: Relevance
“…More recently, several groups have obtained n-type conductivity in Al x Ga 1Àx N:Si with x $ 0.5-1.0 and concluded that Si is a shallow donor even in AlN. [14][15][16][17][18][19] However, in transport measurements, it is not possible to know if free carriers come from the neutral d 0 or negative DX À states of the donor. In electron paramagnetic resonance (EPR) studies of Si-doped AlN, the EPR signal of the shallow donor could only be observed under or after illumination at temperatures below 60 K. 20 The behavior was explained by the negative-U properties of the Si donor with the DX À level at $0.32 eV below the conduction band E C .…”
Section: 10mentioning
confidence: 99%
“…More recently, several groups have obtained n-type conductivity in Al x Ga 1Àx N:Si with x $ 0.5-1.0 and concluded that Si is a shallow donor even in AlN. [14][15][16][17][18][19] However, in transport measurements, it is not possible to know if free carriers come from the neutral d 0 or negative DX À states of the donor. In electron paramagnetic resonance (EPR) studies of Si-doped AlN, the EPR signal of the shallow donor could only be observed under or after illumination at temperatures below 60 K. 20 The behavior was explained by the negative-U properties of the Si donor with the DX À level at $0.32 eV below the conduction band E C .…”
Section: 10mentioning
confidence: 99%
“…[7][8][9][10] Recently, EPR, thermal luminescence and electrical measurements 6 of Si-doped AlN grown by physical vapor transport ͑PVT͒ suggested a model of the shallow Si donor compensated by acceptorlike electron traps within 1 eV below the CBM as an alternative to the assumption of Si DX-center formation.…”
mentioning
confidence: 99%
“…Depending on the Si concentration and the level of carrier compensation, the obtained ionization energy in transport studies are expected to be sample dependent and close to an average of energies of the d 0 state ͑ϳ65 meV͒ and the DX − state of either Si ͑ϳ0.14 eV͒ or O, e.g., ϳ86 meV as determined from an average of two slopes of the temperature dependence of the electron concentration, 7 ϳ180 meV, 8 ϳ60-180 meV, 9 or ϳ250 meV. 10 In summary, we have observed the EPR signal of the shallow Si donor in darkness at temperatures above 95 K. The temperature dependence of the EPR signal in darkness and the persistent signal after illumination suggest that Si is a DX center with the DX − state lying at ϳ78 meV below the shallow donor d 0 state or ϳ0.14 eV below the CBM. With such relatively small thermal activation energy, Si is expected to behave as a shallow dopant in AlN at normal device operating temperatures.…”
mentioning
confidence: 99%
“…Известно, что кремний, встраиваясь на место ка-тиона, является мелким донором с энергией иони-зации ∼ 30 мэВ до x ∼ 0.85 [12]. Поэтому снижение концентрации электронов не объясняется заглублением донорного уровня в AlGaN при возрастании доли Al.…”
Section: обсуждение результатовunclassified